2011
DOI: 10.4401/ag-5035
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical monitoring of volcanic lakes. A generalized box model for active crater lakes

Abstract: In the past, variations in the chemical contents (SO 4 2− , Cl − , cations) of crater lake water have not systematically demonstrated any relationships with eruptive activity. Intensive parameters (i.e., concentrations, temperature, pH, salinity) should be converted into extensive parameters (i.e., fluxes, changes with time of mass and solutes), taking into account all the internal and external chemical-physical factors that affect the crater lake system. This study presents a generalized box model approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…However, Utami et al (2019) show that the rapid variability observed in the gypsum record can only be explained if an additional source of fluid is present locally, because the long residence time of elements in this large volume of brine means that it takes considerable time for compositional disturbances to be visible in the overall lake water composition (cf. Rouwet and Tassi, 2011). Gas bubbling is observed in the lake just in front of the dam, and the conservative element ratios in the various seepage springs suggest a 5% contribution from a different source than the lake (Palmer, 2009).…”
Section: Controls On Seepage Water Compositionsmentioning
confidence: 99%
“…However, Utami et al (2019) show that the rapid variability observed in the gypsum record can only be explained if an additional source of fluid is present locally, because the long residence time of elements in this large volume of brine means that it takes considerable time for compositional disturbances to be visible in the overall lake water composition (cf. Rouwet and Tassi, 2011). Gas bubbling is observed in the lake just in front of the dam, and the conservative element ratios in the various seepage springs suggest a 5% contribution from a different source than the lake (Palmer, 2009).…”
Section: Controls On Seepage Water Compositionsmentioning
confidence: 99%
“…An important parameter in interpreting the historical record is the residence time of water and sulfate in the lake, as this controls how quickly changes will become apparent in the lake, and in the gypsum precipitating from it. To estimate residence time, we use the approach of Rouwet and Tassi (2011), with elemental and isotopic compositions for rain-and groundwater, volcanic gas, lake and seepage water, as well as seepage flux, from van Hinsberg et al (2016). The volcanic gas flux was estimated from the change in Cl content of the lake over time and the Cl content of the volcanic gas, assuming that the surface gas composition is identical to that of the gas entering the bottom of the lake.…”
Section: Oxygen Isotopic Composition Of Stalactite and Gypsum Cement ...mentioning
confidence: 99%
“…Crater lakes are a consequence of a complex interaction between deep/shallow volcanic, hydrothermal, and degassing processes, superficial factors like climate conditions, and morphological elements such as crater geometry (Pasternack and Varekamp, 1997;Christenson et al, 2015). Several disciplines and methods have been applied to understand the processes involved in the formation and evolution of crater lakes, including fluid geochemistry (Dmitri Rouwet and Franco Tassi, 2011;Rouwet et al, 2017), geophysics (Caudron et al, 2012), hydrogeology (Mazza et al, 2015), biology (Mapelli et al, 2015), and limnology (Kling et al, 2015), among others. In the case of some high latitude and high altitude volcanoes, the applicability and frequency of the field methods is restricted to the dry season, impeding the study of the characteristics and dynamics of their crater lakes in a continuous manner.…”
Section: Introductionmentioning
confidence: 99%